The experience of muslim counsellors who counsel unwed muslim pregnant teenagers in Klang Valley, Malaysia - Nursyahidah Khalid (Kulliyyah of Education, International Islamic University Malaysia, 2020)
This qualitative study explored the experience and role of counsellors in handling premarital pregnancy cases among Malay girls in Klang Valley Area. Seven counsellors and four young unwed mothers have been interviewed in this study. Data have been triangulated from interviews, observations and field notes. The findings indicate that counsellors have a significant role in helping young mothers struggling with issues in their life. They are too young and need guidance from their parents and other individuals, where each individual in society can play his/her role as a responsible citizen to create an awareness of healthy sexual knowledge. A comprehensive education and religious approaches should be implemented in the school syllabus and also being guided by parents at home. Sexuality has been seen as a taboo subject which is unfortunately an important aspect for children to understand with respect for their self-knowledge and empowerment. Counsellors who are reported to have used conventional techniques, theories and therapies in their counselling session combined with the Islamic approach has demonstrated to have a positive impact on the young unwed mothers' knowledge of sexuality, self-conduct and self-healing. Most participants agreed that the use of the REBT and the Islamic approach, based on Al-Quran and Sunah combined with the counsellors' unconditional acceptance towards the clients have opened up more room for focusing on emotional condition and healing. The young unwed mothers reportedly made good progress after the counselling sessions with a combination of conventional techniques and Islamic approach. The findings are limited to certain themes which can be explored further for academic and theoretical purposes by other counsellors, policymakers and educators as well as NGO's in helping this vulnerable group of young people who are part of our next generation.